A CFD analysis on using a standardized blade in different mechanical draft cooling towers for geothermal power plants. (December 2021) - Francesconi, Marco; Silei, Tommaso; Gamannossi, Andrea; Provasi, Riccardo; Antonelli, Marco
Highlights: A blade was proposed as a standard model for cooling towers of different sizes. A blade designed for a fan shroud diameter of 8.6 m was simulated in a one of 9.2 m. The analysis relied on an experimentally validated CFD model of the tower. An irregular flow below the blade and recirculation reduced the efficiency. The use of additional appendices made this blade suitable for a larger fan shroud. Abstract: The spare parts standardization without excessively sacrificing energy efficiency may reduce the maintenance costs of components in different geothermal power plants of the same company. This strategy may apply to the blades of the fan used in mechanical draft cooling towers, which usually come in different sizes and are numerous. The case study taken as a reference is a standardized blade, designed for a fan diameter of 8.6 m, used in a 9.2 m diameter fan. The results indicated a decrease in efficiency for the fan with standard blades. Nevertheless, some appendices proved to be effective in limiting the efficiency loss.